Kitāb Ḥall mushkilāt al-Shudhūr - Abū al-Ḥasan ʿAlī b. Mūsā al-Anṣārī al-Andalusī,,Müller, Juliane (De Gruyter, 2024)
The alchemist Abū l-Ḥasan ʿAlī b. Mūsā al-Anṣārī al-Andalusī, known as Ibn Arfaʿ Raʾs (fl. 6th/12th century) is the author of Shudhūr al-dhahab (The Splinters of Gold), one of the most famous poetry collections of Arabic alchemy, which has been the object of no less than thirteen commentaries. The numerous manuscripts of Shudhūr al-dhahab and its commentaries have been read and copied for more than 700 years in various parts of the Islamicate world, from Morocco to India. The very first commentary on Shudhūr al-dhahab was composed by the author Ibn Arfaʿ Raʾs himself. It was transmitted by his disciple Abū l-Qāsim Muḥammad b. ʿAbd Allāh al-Anṣārī under the title Kitāb Ḥall mushkilāt al-Shudhūr (The Unraveling of the Difficulties of 'The Splinters') and is extant in at least 31 manuscripts, of which 27 have been taken into account for this critical edition. This book provides the first edition of Kitāb Ḥall mushkilāt al-Shudhūr, along with an Arabic-English glossary of its alchemical terminology.
10.1515/9783110779356